1998
DOI: 10.1007/s004360050445
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic genotypes discriminate between Babesia canis isolates of differing vector specificity and pathogenicity to dogs

Abstract: The first and second internal transcribed spacers (ITS1, ITS2) as well as the intervening 5.8S coding region of the rRNA gene were characterized in eight Babesia canis isolates of differing geographic origin, vector specificity, and pathogenicity to dogs. The genotypes determined by sequencing segregated into three clearly separated groups close to or near the species level and correspond to the previously proposed subspecies B. canis canis, B. canis vogeli, and B. canis rossi. The three genotypes can be disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(120 citation statements)
references
References 10 publications
4
109
0
7
Order By: Relevance
“…Scrutiny of the results of microscopy and PCR analysis of individual blood sample in the present study revealed that out of 39, 5 microscopic positive B. gibsoni cases remained negative in PCR and the false positivity was 12.82 %. Confirming the vector specific geographic distribution (Uilenberg et al 1989;Zahler et al 1998) of the subspecies of B. canis, several workers reported significant association of Dermacentor reticulatus with B. canis canis prevalent in Europe (Caccio et al 2002;Porchet et al 2007;Zygner et al 2008;Welc-Faleciak et al 2009) and Rhipicephalus sanguineus with B. canis vogeli in tropical and subtropical countries (O'Dwyer et al 2009;Gotsch et al 2009). Using PIRO-A1 and PIRO-B primers Foldvari et al (2005) reported Babesia DNA having 99.8 or 100 % similarity with B. canis canis in sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Scrutiny of the results of microscopy and PCR analysis of individual blood sample in the present study revealed that out of 39, 5 microscopic positive B. gibsoni cases remained negative in PCR and the false positivity was 12.82 %. Confirming the vector specific geographic distribution (Uilenberg et al 1989;Zahler et al 1998) of the subspecies of B. canis, several workers reported significant association of Dermacentor reticulatus with B. canis canis prevalent in Europe (Caccio et al 2002;Porchet et al 2007;Zygner et al 2008;Welc-Faleciak et al 2009) and Rhipicephalus sanguineus with B. canis vogeli in tropical and subtropical countries (O'Dwyer et al 2009;Gotsch et al 2009). Using PIRO-A1 and PIRO-B primers Foldvari et al (2005) reported Babesia DNA having 99.8 or 100 % similarity with B. canis canis in sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…However, genotypic analysis may provide useful indicators to decide for or against possible conspecificity of the unknown Pallas's cat piroplasm to another piroplasm since cross-breeding experiments to show genetic exchange between parasites is not possible (Zahler et al, 1998). Sequence comparison of the conserved 18S rRNA gene allows examination of phylogenetically distant taxa.…”
mentioning
confidence: 99%
“…A second indicator of support against possible conspecificity is the absolute level of genetic differentiation between the unknown Pallas's cat piroplasm in comparison with other related parasites for which species status in accepted (Zahler et al, 1998;Kjemtrup. et al, 2000).…”
mentioning
confidence: 99%
“…On the basis of vector specificity and antigenic properties, B. canis has been subdivided into three subspecies: B. canis canis, B. canis vogeli and B. canis rossi (UILENBERG et al, 1989). Nevertheless, other researchers have adopted phylogenetic criteria to support the taxonomic classification for these organisms into three distinct species (ZAHLER et al, 1998). The red dog tick Rhipicephalus sanguineus, which is recognized as the tick vector of B. gibsoni and B. canis vogeli, is widespread in Brazil, especially in urban areas (SZABÓ et al, 2007).…”
Section: Introductionmentioning
confidence: 99%